Bacillusvelezensis Strains for Protecting Cucumber Plants from Root-Knot Nematode Meloidogyne incognita in a Greenhouse - Anzhela M. Asaturova; Ludmila N. Bugaeva; Anna I. Homyak; Galina A. Slobodyanyuk; Evgeninya V. Kashutina; Larisa V. Yasyuk; Nikita M. Sidorov; Vladimir D. Nadykta; Alexey V. Garkovenko (Plants, 2022)
Meloidogyne incognita Kofoid et White is one of the most dangerous root-knot nematodes in greenhouses. In this study, we evaluated two Bacillus strains (Bacillus velezensis BZR 86 and Bacillus velezensis BZR 277) as promising microbiological agents for protecting cucumber plants from the root-knot nematode M. incognita Kof. The morphological and cultural characteristics and enzymatic activity of the strains have been studied and the optimal conditions for its cultivation have been developed. We have shown the nematicidal activity of these strains against M. incognita. Experiments with the cucumber variety Courage were conducted under greenhouse conditions in 2016–2018. We determined the effect of plant damage with M. incognita to plants on the biometric parameters of underground and aboveground parts of cucumber plants, as well as on the gall formation index and yield. It was found that the treatment of plants with Bacillus strains contributed to an increase in the height of cucumber plants by 7.4–43.1%, an increase in leaf area by 2.7–17.8%, and an increase in root mass by 3.2–16.1% compared with the control plants without treatment. The application of these strains was proved to contribute to an increase in yield by 4.6–45.8% compared to control. Our experiments suggest that the treatment of cucumber plants with two Bacillus strains improved plant health and crop productivity in the greenhouse. B. velezensis BZR 86 and B. velezensis BZR 277 may form the basis for bionematicides to protect cucumber plants from the root-knot nematode M. incognita.